Original paperTopical microemulsion containing Punica granatum extract: its control over skin erythema and melanin in healthy Asian subjects - Parveen, Rashida; Akhtar, Naveed; Mahmood, Tariq (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: Punica granatum is apotent source of polyphenolic compounds with strong free radicals scavenging activity. The skin lightening effects of Punica granatum are assumed due to ellagic acid which acts by chelating copper at the active site of tyrosinase. Aim: To explore a topical microemulsion (O/W) of pomegranate ( Punica granatum ) extract for its control on skin erythema and melanin. Material and methods: Microemulsions were formulated using a polysorbate surfactant (Tween 80®) along with cosurfactant (propylene glycol) and were characterized regarding their stability. The placebo microemulsion (without extract) and the active microemulsion (containing Punica extract) were applied in a split face fashion by the volunteers (n = 11) for a period of 12 weeks. Skin erythema and melanin were measured at baseline and after every 15 days to determine any effect produced by these formulations. Results: Active formulation showed a significant impact on skin erythema and melanin (p < 0.05). Conclusions : This study reveals that a suitable topical formulation like microemulsion could employ the Punica granatum extract for conditions where elevated skin melanin and erythema have significantly prone skin physiology.